The effect of lysine level or methionine/copper/manganese on osteochondrosis lesions and cartilage properties in pigs - N Z Frantz; G Andrews; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
A total of 120 gilts (PIC 327 × 1050; 89.2 lb initial BW) were used in a 3 × 2 factorial, 84-d study to determine the effect of lysine (Lys) fed either below the calculated requirement (0.8% true ileal digestible (TID) Lys Phase I and 0.6% TID Lys Phase II), at requirement (1.0% TID Lys Phase I and 0.8% TID Lys Phase II), or above the requirement (1.3% TID Lys Phase I and 1.1% TID Lys Phase II) with standard concentrations or with high added methionine (Met, 1 %), copper sulfate (Cu, 250 ppm), and manganese sulfate (Mn, 220 ppm) on the occurrence and severity of osteochondrosis (OC) lesions, growth performance, soundness, carcass traits, and several cartilage criteria. Upon completion of the feeding period, pigs were harvested and the distal aspect of the left humerus and femur were evaluated by gross examination for OC lesions. The external surface was evaluated for abnormalities and received a severity score. For the external femur evaluation, increasing dietary Lys concentration tended (linear, P<0.08) to increase the number of abnormalities and there was a numerical trend for an increased severity score (P<0.13) with increasing dietary Lys. The addition of high Met/Cu/Mn to the diet reduced the number of abnormalities (P<0.02) and severity score (P<0.01) at the external femur compared to pigs fed diets with standard concentrations of Met/Cu/Mn. At the external humerus, increasing dietary Lys increased both the number of abnormalities (linear, P<0.01) and severity score (linear, P<0.01). The addition of high Met/Cu/Mn to the diet reduced the number of abnormalities (P<0.03) and severity score (P<0.03) for the external humerus. Increasing dietary Lys concentration or high-added Met/Cu/Mn had no effect (P>0.14) on the number of faces with lesions at the femoral growth plate or the severity score (P>0.19). The number of faces with lesions and severity score at the humerus articular cartilage was unaffected by increasing dietary Lys concentration (P>0.16) or the addition of high Met/Cu/Mn to the diet (P>0.37). The total faces with lesions were not impacted by increasing dietary Lys concentration (P>0.78) or additional high Met/Cu/Mn (P>0.86). The total abnormalities (external and number of faces) tended to increase with increasing dietary Lys (linear, P<0.12). The addition of high Met/Cu/Mn did not affect the total number of abnormalities (P>0.16). The total severity score for both external and OC evaluation increased with increasing dietary Lys concentration (linear, P<0.01). The addition of high Met/Cu/Mn decreased the total severity score (P<0.02) compared to pigs fed diets with standard concentrations of Met/Cu/Mn. Finally, increasing dietary Lys concentration increased the sum (linear, P<0.05) of abnormalities and total severity score. The addition of high Met/Cu/Mn tended (P<0.09) to reduce the overall severity score compared to pigs fed diets with standard concentrations of Met/Cu/Mn. In conclusion, feeding growing gilts dietary Lys to maximize growth performance may increase the severity of OC lesions, while a diet with additional Met/Cu/Mn may aid in the reduction of OC severity scores.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Amino acids; Cartilage; Health; Osteochondrosis